# How to show that if either $\{a_k\}$ or $\{b_k\}$ converges, equality holds. (lim sup, lim inf) [closed]

I am studying Real analysis by the textbook, Measure and Integral: an introduction to real analysis by Wheeden and Zygmund. This is my first time to study mathematical analysis. However, instructor gave me assignments which is solving even problems in Chapter 1's exercises.

I solved $2$, and $4$ (a), (b), (c) but failed to solve $4$ (d). Can someone help me?

4.

(b) Show that $\limsup_{k\to\infty}(a_k+b_k)\le\limsup_{k\to\infty}a_k + \limsup_{k\to\infty}b_k$.

(c) If $\{a_k\}$ and $\{b_k\}$ are nonnegative, bounded sequences, show that $\limsup_{k\to\infty}(a_kb_k)\le(\limsup_{k\to\infty}a_k)(\limsup_{k\to\infty}b_k)$.

(d) (1) Give examples for which the inequalities in parts (b) and (c) are not equalities. (2) Show that if either $\{a_k\}$ or $\{b_k\}$ converges, equality holds in (b) and (c).

I solved (b) and (c) and (d)-(1).

Please let me know how to prove (d)-(2). Thank you very much.

## closed as off-topic by Siminore, Michael Hoppe, Bobson Dugnutt, Watson, Harish Chandra RajpootMar 7 '16 at 19:40

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – Siminore, Michael Hoppe, Bobson Dugnutt, Watson, Harish Chandra Rajpoot
If this question can be reworded to fit the rules in the help center, please edit the question.

• Assume $a_k\to a*$ and the subsequence $b_{k_n}$ converges to $\limsup b_k$. What can you say about the limit of $a_{k_n} + b_{k_n}$? – user251257 Mar 7 '16 at 16:14

Suppose that $a_k \to A$. Let $\epsilon > 0$ be fixed, and choose $N$ so that $k \ge N$ implies $|a_k - A| < \epsilon$. Let $n \ge N$ and let $k \ge n$. Then $A - \epsilon < a_k$ so that $$b_k = (b_k + A - \epsilon) - A + \epsilon \le (b_k + a_k) + \epsilon \le \sup_{j \ge n} (a_j + b_j) - A + \epsilon.$$ The right-hand-side does not depend on $k$, so take the supremum over all $k \ge n$ to find $$A + \sup_{k \ge n} b_k \le \sup_{j \ge n} (a_j + b_j) + \epsilon.$$ Both sides are nondecreasing in $n$ so we may let $n \to \infty$ to find $$A + \limsup_{k \to \infty} b_k \le \limsup_{k \to \infty} (a_k + b_k) + \epsilon.$$ Here $\epsilon > 0$ is arbitrary so take $\epsilon \to 0^+$ to get $$A + \limsup_{k \to \infty} b_k \le \limsup_{k \to \infty} (a_k + b_k).$$

• Thank you for answer. I think I need more time to understand. – Danny_Kim Mar 9 '16 at 7:05

Use the definition of $\limsup$:

$g_k=\sup _{n\geq k}\left \{ a_n \right \}$

$h_k=\sup _{n\geq k}\left \{ b_n \right \}$

If $a_n$ and $b_n$ converge to $L$ and $M$, resp. then $g_k$ and $h_k$ converge to $L$ and $M$, resp. as well. (why?), so now using the sum formula for limits we get

$\lim_{k\to \infty }(g_k+h_k)=\lim_{k\to \infty }g_k+\lim_{k\to \infty }h_k$,

which is what we want.

• Thank you for answer. I think I need more time to understand. – Danny_Kim Mar 9 '16 at 7:05